Multifunctional vanadium nitride@N-doped carbon composites for kinetically enhanced lithium–sulfur batteries. (7th March 2018) - Zhu, Lin; Li, Chuanchuan; Ren, Wenjiao; Qin, Mingyang; Xu, Liqiang
Abstract : VN@N-doped carbon composite was fabricated as sulfur host to enhance the redox kinetics of Li–S batteries, which displayed remarkable electrochemical performances. Abstract : On the heels of growing demand for electric vehicles and storage applications, lithium–sulfur (Li–S) batteries with a high energy density have attracted significant attention. Enhancing the redox reaction kinetics, depressing the shuttle effect and the controlled deposition of lithium sulfide are simultaneously in urgent requirement for high-performance Li–S batteries. Herein we report a vanadium nitride@N-doped carbon nanowire (VN@C) hybrid composite that combines the merits of polar VN and conductive carbon to achieve fast sulfur species transformation, high adsorption of polysulfides and restricted self-discharge behavior. Benefiting from the structure, the resulting compound demonstrates exceptional performance with a high discharge capacity of 875 mA h g −1 at 1C, a prominent rate capability of 550 mA h g −1 at 6C and remarkable electrochemical performances even with a high sulfur loading (4.2 mg cm −2 ). This conductive VN@C composite and its electrochemical performance could offer novel insights for further design of Li–S batteries.